Occurrence, distribution and activity of alkaline phosphatase producing bacteria in freshwater fishpond ecosystems - Barik, S K; Purushothaman, C S (Indian Journal of Fisheries, 2011)
In the freshwater fish ponds, Bacillus spp. were found to be the dominant bacteria producing phosphatase. The alkaline phosphatase activity of sediment was always higher than that of water. In the case of water, though the ’dissolved’ alkaline phosphatase activity was lower than the ’total’ alkaline phosphatase activity, the former was nevertheless unimportant as it constituted about 20% of the ’total’ activity.